Theoretical Engagement of Masculinities in Development Organizations Working with Men: A Qualitative Document Analysis of Instituto Promundo and Sonke Gender Justice - Sonnenberg-Smith, Jamie-Lee (Université d'Ottawa / University of Ottawa, 2019)
This research investigates two major organizations that place a focus on masculinities as a strategy to improve gender equality; Instituto Promundo and Sonke Gender Justice. To begin, a literature review of the gendered dynamics and masculinities context in Brazil and South Africa is presented to situate the historical and current landscape of where each organization operates. This thesis research investigates Promundo and Sonke using qualitative document analysis methodology, with a theoretical framework informed by relevant masculinities scholarship and the specific contexts of masculinities in Brazil and South Africa. This approach provides insights into the history, evolution, and application of theoretical perspectives and the organizational structures that influence how masculinities are discussed and practiced when implementing programs in Brazil and South Africa. The research shows that Promundo and Sonke integrate most of the key masculinities themes and key concepts, with a comparative lens of each organization, and highlighting key gaps and why their inclusion has the potential to strengthen each organization’s position as world leaders in masculinities and gender equality.
Keywords: Masculinities; Masculinities Theories; Gender; Gender Equality; Men; Sonke Gender Justice; Instituto Promundo; Development